DEKONSTRUKSI OTORITAS KEAGAMAAN DI ERA KECERDASAN BUATAN (POLA NEGOSIASI EPISTEMOLOGI FIQIH MAHASISWA PAI TERHADAP GENERATIVE AI) - Nova Dwi Lestari; Rezky Amanda; Desi Firmasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the dynamics of shifting legitimacy in Islamic religious authority during the digital transformation era through a deconstructive analysis of Islamic Religious Education (PAI) students' interaction patterns with Generative Artificial Intelligence (GenAI) instruments. The rapid advancement of artificial intelligence technologies—such as ChatGPT, Claude, and Perplexity—presents new epistemological challenges to conventional scholarly hierarchies and traditional fiqh reasoning traditions. Drawing on a qualitative-phenomenological design combined with Jacques Derrida's deconstructive perspective and Heidrun Campbell's digital religious authority framework, this investigation involves 45 PAI students within Islamic higher education institutions. The research findings indicate that GenAI functions not merely as a tool for exploring Islamic legal information, but also triggers a deconstruction of traditional authority structures rooted in scholarly chains of transmission (sanad), Arabic proficiency, and pesantren traditions. Three adaptation patterns of PAI students' fiqh epistemological reasoning were identified: (1) Conformative-Instrumental, where AI recommendations are accepted for efficiency without disregarding foundational norms; (2) Critical-Verificationist, where AI syntheses are treated as preliminary hypotheses critically tested against turath literature and scholars' authority; and (3) Hybrid-Eclectic, which integrates algorithmic logic with classical fiqh rationality. This study concludes that the digital transformation demands a restructuring of Islamic law pedagogy in higher education to foster an adaptive digital-epistemological literacy capability in the age of artificial intelligence.